Numerical analysis on the effect of bifurcation angle and inlet velocity on the distribution uniformity performance of consecutive bifurcating fluid flow distributors. (April 2018) - Cao, Jun; Kraut, Manfred; Dittmeyer, Roland; Zhang, Li; Xu, Hong
Abstract: 2-D numerical models have been used to analyze flow distribution performance in consecutive bifurcating fluid flow distributors according to constructal theory. The quantitative analysis of flow distribution uniformity performance for Y shape distributors with different bifurcation angles as well as inlet velocities are evaluated with water as working fluid, a hypothesis on the mechanism for the maldistribution is also presented. It is found that the flow distribution uniformity deteriorates with the increase of bifurcation angles from 15° to 90°, and the worst performance occurs when bifurcation angle is 90°, where the largest pressure drop also appears. Furthermore, the flow distribution performance also decreases with increasing inlet velocity for the same distributor. Finally, an improvement to obtain more uniform flow uniformity for the T shape distributor is proposed by 'shrinking' the vertical channel width of each bifurcation. The conclusions obtained in this paper are potentially helpful for the design of fluid distributors for multi channel devices.